2007
DOI: 10.1252/jcej.07we180
|View full text |Cite
|
Sign up to set email alerts
|

The Structural Design of Electrode Materials for High Energy Lithium Batteries

Abstract: Lithium batteries are used to power a diverse range of applications from small compact devices, such as smart cards and cellular telephones to large heavy duty devices such as uninterrupted power supply units and electric-and hybrid-electric vehicles. This paper briefly reviews the approaches to design advanced materials to replace the lithiated graphite and LiCoO 2 electrodes that dominate today's lithiumion batteries in order to increase their energy and safety. The technological advantages of lithium batter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…These compositions can be represented as Li[M 1– x Li x ]O 2 , where the elements in the brackets represent the composition of the transition-metal layer. It has been proposed that these Li[M 1– x Li x ]O 2 samples are composed of two phases, namely, a parent trigonal LiMO 2 phase (space group R 3̅ m ), and a monoclinic Li 2 MnO 3 phase (space group C 2/ m ). The higher capacity of Li[M 1– x Li x ]O 2 is believed to be partially due to the monoclinic Li 2 MnO 3 phase, which acts to stabilize the structure of the trigonal LiMO 2 phase during Li-extraction (charge). On the other hand, some researchers believe that the two components, Li 2 MnO 3 and LiMO 2 , exist as a solid solution. , As a result, much debate has been spurred over the atomic structure of these materials and how they relate to the materials’ electrochemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…These compositions can be represented as Li[M 1– x Li x ]O 2 , where the elements in the brackets represent the composition of the transition-metal layer. It has been proposed that these Li[M 1– x Li x ]O 2 samples are composed of two phases, namely, a parent trigonal LiMO 2 phase (space group R 3̅ m ), and a monoclinic Li 2 MnO 3 phase (space group C 2/ m ). The higher capacity of Li[M 1– x Li x ]O 2 is believed to be partially due to the monoclinic Li 2 MnO 3 phase, which acts to stabilize the structure of the trigonal LiMO 2 phase during Li-extraction (charge). On the other hand, some researchers believe that the two components, Li 2 MnO 3 and LiMO 2 , exist as a solid solution. , As a result, much debate has been spurred over the atomic structure of these materials and how they relate to the materials’ electrochemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…In earlier research in 2010, several published articles reported nanomaterial or nanoscale TMO showing similar performance to the commercial material. [103][104][105][106][107][108] But the attention was dealt with commercial anxiety due to the intrinsic property of the nanomaterials. Nanomaterials possess a high surface-tovolume ratio and high porosity.…”
Section: Transition Metal Oxide Nanomaterialsmentioning
confidence: 99%
“…Some groups have reported Li[Li x M 1-x ]O 2 to be a single-phase layered oxide solid solution, 1 while others claim that these materials are composed of two phases, namely Li 2 MnO 3 and LiMO 2 . 2,3 To address this issue, we have used aberration-corrected STEM imaging and STEM computer simulations, as well as a novel STEM electron diffraction technique, called D-STEM, 4 to study the lithium-rich composition Li[Li .2 Mn .6 Ni .2 ]O 2 .…”
Section: Introductionmentioning
confidence: 99%